The Effect of Squat Thrust Exercise on Smash Outcomes in Volleyball Athletes - Renanto Renanto; Yudi Saputra (Universitas PGRI Palembang, 2023)
This study aims to determine whether there is an influence between the squat thrust exercise on the smash results of volleyball beginner athletes at ISPRI Palembang CLUB. In this study the method used was an experiment with the One Group Pre test Post test design, namely statistics to determine the effect between two symptoms, the data collection technique used was the test. Smash test to measure volleyball smash results. The population in this study were volleyball beginner athletes at ISPRI Palembang club, totaling 20 athletes and the sample in this study were 20 volleyball athletes at club ISPRI Palembang. The data obtained were analyzed using the experimental formula. The results of the experimental analysis obtained for the initial test (pre-test) average value is 102 with a standard deviation of 12 while for the final test (post-test) average value is 106 with a standard deviation of 9. So it can be stated that there is an effect of squat thrust training on the results of the athlete's smash hit, a significant test was carried out and the tcount value was 5.425 and the ttable price was 1.725. So tcount > ttable, thus Ha is accepted and Ho is rejected, which means that there is a significant effect of squat thrust training on the athlete's smash results at ISPRI club Palembang.